DIAGNOSIS OF AN ENVIROMENTAL SYSTEM: THE CASE OF HYDROGRAPHICAL MICRO BASIN OF RIBEIRÃO DAS MARRECAS IN LONDRINA – PR – BRAZIL - Ricardo Aparecido Campos; Walquíria Machado; Nilza Aparecida Freres Stipp (Sociedade & Natureza)
The human survival is closely connected to the use we do of our natural resources existing inour planet, in a way that this connection depends on the consumption habits and apprehensionof these goods. During the last century (XX), we noticed a boom of technology and a greatchanging in the habits of the world population. With the information globalization andknowledge, the environmental situation in the planet was more evident, and we concluded thatthe mankind should rethink the model of exploration of the natural resources. (Stockholm,Rio-92, Agenda 21 among others), and even the social paradigms. The proposal of this workis make a factual approach in this ocean of knowledge and discussions about theenvironmental problems currently presented in our society. It was chosen as a study unity theHydrographic basin, specifically the physical processes presented at Ribeirão das Marrecasmicro basin river. Collecting the data, basically a physical environmental inventory,characterizing the environment as most detailed as possible of the micro basin by consultingthe cartographic documents available and bibliographic information. To the developing of themicro basin hydrographical of Ribeirão das Marrecas, it was necessary the confection ofseveral themes letters. Each item of the inventory was translated into basic themes maps:geological, geo morphological, downward slopes maps, hydrographic, climatologically, theuse of the soil and pedological. The intervention unit “hydrographical basin” presents advantages and disadvantages. The main advantage is that this territorial unit relates theeffects/causes of the environmental more clearly and easier measuring. So, we intend toestablish the recovery proposals presenting some mitigating alternatives or solving conflictsin the area of the micro basin. Due the region peculiarities, concerning to the dynamiceconomical and social factors, it becomes imperative that the civil responsibility takes it overin response to the environmental passive, whether they come from naturals means or from theaction of man.